2014
DOI: 10.1002/jsfa.6822
|View full text |Cite
|
Sign up to set email alerts
|

Management practices and forage quality affecting the contamination of milk with anaerobic spore-forming bacteria

Abstract: BACKGROUND Anaerobic spore‐forming bacteria (ASFB) in milk derive from the farm environment, and the use of silages and management practices are the main responsible of milk ASFB contamination. The aim of this study was to evaluate the relationships between feeding, milking routine and cow hygiene and milk and Grana Padano cheese (produced with and without lysozyme) ASFB contamination. RESULTS The study involved 23 dairy farms. ASFB in corn silage were on average 2.34 ± 0.87 log10 MPN g−1. For grass, Italian r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 25 publications
5
40
1
Order By: Relevance
“…Borreani and Tabacco and Vissers et al . reported a higher number of clostridia spores in peripheral than core corn silage samples, confirming that aerobic deterioration could raise concentrations of clostridia spores in silages, thus increasing the possible risk of milk contamination . In accordance with this, a higher concentration of fermentation end‐products ascribable to clostridia activity was observed in peripheral than core samples, particularly in samples collected from lateral parts of the working face.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Borreani and Tabacco and Vissers et al . reported a higher number of clostridia spores in peripheral than core corn silage samples, confirming that aerobic deterioration could raise concentrations of clostridia spores in silages, thus increasing the possible risk of milk contamination . In accordance with this, a higher concentration of fermentation end‐products ascribable to clostridia activity was observed in peripheral than core samples, particularly in samples collected from lateral parts of the working face.…”
Section: Discussionmentioning
confidence: 52%
“…However, data variability associated with PC2 subject‐based scores (standard deviations of 0.43, 0.93 and 1.44 for core, lateral and apical samples, respectively) suggested that fermentation end‐products associated with clostridia strains occurred at high concentrations also in core and apical samples. A possible transfer of clostridia spores could occur from silage to milk via faecal contamination of the teats, with negative impact on cheese quality …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, while for cow's milk, high clostridial spore counts are mainly recorded in winter, due to silage feeding (Driehuis 2013;Zucali et al 2015), for ewe's milk, high MPN counts have also been observed in summer. This could be due to environmental factors, husbandry and feeding practices other than silage feeding, such as wool spore contamination, milking hygiene, and an incorrect management of the bedding, especially during anomalous summer seasons (i.e., particularly rainy or dry).…”
Section: Discussionmentioning
confidence: 99%
“…In order to create an easy-to-use tool for multiple quality aspects (animal welfare, environmental and economic sustainability of dairy farms, microbiological, nutritional and nutraceutical quality of milk), 19 variables were selected according to their informative characteristics and importance, resulted from previous studies Zucali et al 2014), and to their prevalence and variability in the sample (Figure 1).…”
Section: Multi-dimensional Assessment and Scoring Systemmentioning
confidence: 99%